DOES FLIPPED LEARNING WORK? A CASE FOR PRIVATE UNIVERSITY IN INDONESIA - Basori Basori; Diah Wihardini (Getsempena English Education Journal, 2020)
This study sought to find out the result of implementing Flipped Learning in pre-university English class in one of private universities in Indonesia. The study answers the question on to what extend the flipped learning work or fail when being implemented in the respective class. The data which were the result of pre-test and post-test were collected using quantitative method. To analyse the data, a non-parametric approach was used to analyse the impact of the FL approach on student performance in the EPS program. The difference between the pre- and test- scores was calculated and used in a hypothesis testing method using the Mann-Whitney-Wilcoxon Test. The result indicated that there is no significance difference between the treatment group and the control group. Some possible reasons why the insignificance happen are presented as well as some recommendations towards future studies in FL context.